Wind-Driven Coastal Upwelling in the Southern Coast of Yogyakarta - Faizal Rachman; Ratih Ida Adharini; Riza Yuliratno Setiawan; Indun Dewi Puspita; Endy Triyannanto (Jurnal Perikanan Universitas Gadjah Mada, 2018)
Satellite measurement provides synoptic view of sea surface wind and can be used to study variability of coastal upwelling. Here we analyzed data of 12 years of satellite-derived sea surface wind, sea surface temperature (SST), and sea surface chlorophyll-a (Chl-a) to examine the spatial and temporal distributions of coastal upwelling off the Yogyakarta waters. Results show that upwelling occurs during the Southeast Monsoon (SEM) season. During this season, the Yogyakarta waters are dominated by strong wind speed (~7 m/s) and SST cooling (25 °C). Whereas during the Northwest Monsoon (NWM) season the low wind speed (<4 m/s) no longer favor upwelling and SST cooling. We suggest that as the Yogyakarta coastline is oriented east-west, northwesterly winds result in downwelling condition at the coast, while southeasterly winds lead to the offshore Ekman transport of surface water and subsequent upwelling.